Heat shock response and homeostatic plasticity - Karunanithi, Shanker; Brown, Ian R. (Frontiers in Cellular Neuroscience, 2015)
Heat shock response and homeostatic plasticity are mechanisms that afford functional stability to cells in the face of stress. Each mechanism has been investigated independently, but the link between the two has not been extensively explored. We explore this link. The heat shock response enables cells to adapt to stresses such as high temperature, metabolic stress and reduced oxygen levels. This mechanism results from the production of heat shock proteins (HSPs) which maintain normal cellular functions by counteracting the misfolding of cellular proteins. Homeostatic plasticity enables neurons and their target cells to maintain their activity levels around their respective set points in the face of stress or disturbances. This mechanism results from the recruitment of adaptations at synaptic inputs, or at voltage-gated ion channels. In this perspective, we argue that heat shock triggers homeostatic plasticity through the production of HSPs.